City linkage. Art and culture fostering urban futures. - (:unkn) unknown (Jovis, 2016)
How do we want to live together? How can citizens directly participate in city politics? How can we shape cities so that they are livable? These questions are more relevant than ever given current processes of transformation; our cities are rapidly changing as a result of both climate change and globalization. Which role do artist-run spaces and self-organized cultural projects play in the search for solutions to the city of the future? In City Linkage artists, researchers, activists, and theorists introduce successful international examples of urban development, showing the degree to which contributions from the arts and cultural sectors can support the manifestation of a sustainable city.
Keywords: Stadtraum; Kultur; Kunst; Reflexion; Öffentlicher Raum; Stadtentwicklung; Beispielsammlung; Kunstprojekt; Kunstaktion; Intervention; Raumaneignung; Kreativität; Nachhaltige Entwicklung